PENGEMBANGAN MEDIA KOMIK MENYAJIKAN PERUBAHAN DIALOG MENJADI TEKS PROSEDUR DI KELAS IX MTS AL-‘IMAROH CIKARANG UTARA - Sultonah, Nur Sultonah; Lestari, Dinda Permata; Alfath, Khoirunnisa Syahadati; Rosalina, Sinta (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2025)
This study aims to develop comic-based learning media for ninth-grade students at MTS Al-'Imaroh Cikarang Utara. The comic, adapted from the short story "Hidup Bersih dengan Mencuci Tangan" (Clean Living by Washing Hands), is designed to assist in understanding procedural texts through engaging illustrations and narratives. The results indicate that the comic effectively enhances students' comprehension and motivation. Positive feedback from students and teachers suggests